1984
DOI: 10.1203/00006450-198408000-00024
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Auditory Brainstem Response Testing in Neonatal Populations

Abstract: SummaryThe use of auditory brainstem response (ABR) for assessment of hearing in the neonate has not been without challenge. Although numerous articles have appeared, agreement regarding the utility of neonatal ABR testing does not exist. In review of the current studies and commentaries, a clear majority are favorable to neonatal ABR testing. These studies along with current test procedures are discussed. (38); procedures for the assessment of that potential were initiated. Since 1975, the research reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Approximately 1 child in every 1000 live births suffers from a serious congenital hearing impairment [7,29]. The prevalence of hearing impairment is much higher among the population of neonatal intensive care units with figures of 1% reported in Great Britain [7,9], 1.5% in the Netherlands [47] and 2% in the USA [6].…”
Section: Principles For Screening Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 1 child in every 1000 live births suffers from a serious congenital hearing impairment [7,29]. The prevalence of hearing impairment is much higher among the population of neonatal intensive care units with figures of 1% reported in Great Britain [7,9], 1.5% in the Netherlands [47] and 2% in the USA [6].…”
Section: Principles For Screening Programmesmentioning
confidence: 99%
“…The conventional auditory brainstem evoked response is the gold standard which is used for testing hearing [6,13,20]. The use of auditory brainstem responses (ABR) was first reported by Jewett et al in 1970 [21].…”
Section: Conventional Auditory Brainstem Evoked Responsementioning
confidence: 99%
“…By contrast, researchers in two of the six studies found evidence of peripheral delays as indicated by prolonged latencies of Wave I (Nakamura et al, 1985;Streletz et al, 1986). In three studies, investigators looked specifically at the question of threshold elevation and found no relation with elevated bilirubin levels (Cox et al, 1984;Lenhardt et al, 1984;Roberts et al, 1982), although Cox and Roberts did not measure the ABR at peak bilirubin levels.…”
Section: Risk Factorsmentioning
confidence: 94%
“…Since the description of ABRs (Jewett & Williston, 1971), the procedure has been widely used in the evaluation of auditory nerve integrity in children. Thus, in the absence of reliable behavioral audiometric methods for newborns, the technique has become popular as a hearing screening test for neonatal intensive care (NICU) survivors (Cox, 1984). This has led to the use of the ABR to evaluate hearing in populations that are not testable using traditional methods.…”
Section: Improvements In Neonatal Intensive Carementioning
confidence: 99%
“…Brainstem acoustic evoked potentials (BAEP) to different stimulus intensities have proved to be a reliable tool in the early diagnosis of hearing impairment in high-risk infants (1,2,3,5,15,17,18). Abnormalities ofwaveform and prolongation of interpeak latencies are objective indicators of brainstem involvement in various neuropediatric diseases, for example in post-asphyxiated children, dysraphic malformations or during neurointensive treatment (3,7,8,13,19 (4,10,11,14,15,17,20).…”
Section: Introductionmentioning
confidence: 99%